Understanding refugee and immigrant health literacy and beliefs toward antimicrobial resistance - Joseph Ladines-Lim; Elizabeth Scruggs-Wodkowski; Tessa Adžemović; Rachel Croxton; Ron Romero; Michael Lukela; Krishna Rao; Preeti Mehrotra; Payal K. Patel (Cambridge University Press, 2023)
Refugee and migrant populations have increased vulnerability to antimicrobial resistance, yet stewardship guidance is lacking. We addressed this gap through a cross-sectional survey, finding that these populations and immigrants from low and middle-income countries had lower health literacy on the issue compared to native-born Americans and those from high-income countries.